An insight into the vaginal microbiome of infertile women in Bangladesh using metagenomic approach - Hasan, Zahid; Netherland, Michael; Hasan, Nur A.; Begum, Nurjahan; Yasmin, Mahmuda; Ahmed, Sangita (Frontiers in cellular and infection microbiology, 2024)
The dysbiosis of vaginal microbiota is recognized as a potential underlying factor contributing to infertility in women. This study aimed to compare the vaginal microbiomes of infertile and fertile women to investigate their relationship with infertility. Metagenomic analysis was conducted on samples from 5 infertile and 5 fertile individuals using both amplicon 16S and metagenomics shotgun sequencing methods. In the infertile group, the bacterial community was primarily represented by three major bacterial genera: (79.42%), (12.56%) and (3.33%), whereas, the fertile group exhibited a more diverse composition with over 8 major bacterial genera, accompanied by significantly reduced abundance of (48.79%) and (6.98%). At the species level, higher abundances of and were observed in the infertile group. Regarding the microbiome composition, only one fertile and two infertile subjects exhibited the healthiest Community State Types, CST-1, while CST-3 was observed among two infertile and one fertile subject, and CST-4 in three other fertile and one infertile subject. Overall, alpha diversity metrics indicated greater diversity and lower species richness in the control (fertile) group, while the infertile group displayed the opposite trend. However, beta-diversity analysis did not show distinct clustering of samples associated with any specific group; instead, it demonstrated CST-type specific clustering. Shotgun metagenomics further confirmed the dominance of Firmicutes, with a greater abundance of species in the infertile group. Specifically, and were identified as the most dominant and highly abundant in the infertile group. Fungi were only identified in the control group, dominated by (62.5%). Metagenome-assembled genomes (MAGs) corroborated read-based taxonomic profiling, with the taxon identified exclusively in disease samples. MAG identities shared by both groups include Shamonda orthobunyavirus, , Human endogenous retrovirus K113, , and . Interestingly, the healthy microbiomes sequenced in this study contained two clusters, and , not found in the public dataset. In conclusion, this study suggests that lower species diversity with a higher abundance of and , may contribute to female infertility in our study datasets. However, larger sample sizes are necessary to further evaluate such association.